6‐nitrodopamine is a major endogenous modulator of human vas deferens contractility. (17th August 2022) - Britto‐Júnior, José; da Silva‐Filho, Walter Pinto; Amorim, Amanda Consulin; Campos, Rafael; Moraes, Manoel Odorico; Moraes, Maria Elisabete A.; Fregonesi, Adriano; Monica, Fabiola Z.; Antunes, Edson; De Nucci, Gilberto
Abstract: Background: Rat isolated vas deferens releases 6‐nitrodopamine (6‐ND), and the spasmogenic activity of this novel catecholamine is significantly reduced by tricyclic compounds such as amitriptyline, desipramine, and carbamazepine and by antagonists of the α1 ‐adrenergic receptors such as doxazosin, tamsulosin, and prazosin. Objectives: To investigate the liberation of 6‐ND by human epididymal vas deferens (HEVDs) and its pharmacological actions. Methods: The in vitro liberation of 6‐ND, dopamine, noradrenaline, and adrenaline from human vas deferens was evaluated by LC‐MS/MS. The contractile effect of the catecholamines in HEVDs was investigated in vitro. The action of tricyclic antidepressants was evaluated on the spasmogenic activity ellicited by the catecholamines and by the electric‐field stimulation (EFS). The tissue was also incubated with the inhibitor of nitric oxide (NO) synthase L‐NAME and the release of catecholamines and the contractile response to EFS were assessed. Results: 6‐ND is the major catecholamine released from human vas deferens and its synthesis/release is inhibited by NO inhibition. The spasmogenic activity elicited by EFS in the human vas deferens was blocked by tricyclic antidepressants only at concentrations that selectively antagonize 6‐ND induced contractions of the human vas deferens, without affecting the spasmogenic activity induced by dopamine, noradrenaline, and adrenaline in this tissue. Incubation of the vas deferens with L‐NAME reduced both the 6‐ND release and the contractions induced by EFS. Discussion and conclusion: 6‐ND should be considered a major endogenous modulator of human vas deferens contractility and possibly plays a pivotal role in the emission process of ejaculation. It offers a novel and shared mechanism of action for tricyclic antidepressants and α1 ‐adrenergic receptor antagonists.